Pengembangan Media Video Virtual Reality Berbasis Camera Go Pro 360º dalam Pembelajaran Tari Lenggang Patah Sembilan di SMA Negeri 113 Jakarta Timur - Belinda Putri Amalya Pranoto; Triana, Dinny Devi; Cahyadi, Ojang (Program Studi Pendidikan Tari FBS UNJ, 2022)
The purpose of this study was to determine how much influence the use of virtual reality video media based on the Go Pro 360º camera which is used as a dance learning medium for students and to assist the instructor as a new learning medium based on the Go Pro 360° camera, which is more efficient technology. This research is a Research & Development method with the ADDIE model (Analysis, Design, development, Implementation, Evaluation). The product resulting from this research is a virtual reality video based on the Go Pro 360º camera featuring the Lenggang Patah Sembilan dance. The results obtained from this study are based on material experts 100%